Evaluation of Daily Creel and Minimum Length Limits for Black Crappie and Yellow Perch in Wisconsin. (12th January 2015) - Mosel, Kyle J.; Isermann, Daniel A.; Hansen, Jonathan F.
Abstract: Harvest regulations for Black Crappie Pomoxis nigromaculatus and Yellow Perch Perca flavescens in the northern USA and Canada have not been thoroughly evaluated, and specific guidance regarding where minimum length limits (MLLs) might improve these fisheries is lacking. We examined whether: (1) transitioning from an aggregate statewide daily creel limit of 25 panfish to species‐specific daily creel limits of <25 fish or implementing statewide MLLs could reduce harvest of Black Crappie and Yellow Perch in Wisconsin by ≥25%, and (2) MLLs would improve yield by ≥10% and mean TL of harvested fish by ≥25 mm in Wisconsin fisheries. Creel surveys indicated that ≥94% of Wisconsin anglers did not harvest a Black Crappie or Yellow Perch, and ≤0.12% of anglers harvested a daily creel limit of 25 fish. Daily creel limits would need to be ≤7 fish/ angler to reduce harvest by ≥25%. Statewide MLLs would need to be ≥229 mm for Black Crappie and ≥203 mm for Yellow Perch to reduce harvest by ≥25%, but predicted responses to MLLs varied among simulated populations. In general, MLLs were not predicted to improve yield, indicating that growth overfishing was not a widespread problem. Minimum length limits could improve mean TL of harvested fish, but increases ≥25 mm were only observed under 254‐mm and 279‐mm MLLs, and anglers would have to accept predicted reductions in harvest of ≥30% to achieve these improvements. A 229‐mm MLL offered a more equitable trade‐off between increases in mean TLs of harvested fish (11–21‐mm improvements) and reductions in harvest (22–37% reductions). Our modeling provides a framework for managers to make more informed decisions regarding harvest regulations, but more information regarding angler preferences is needed for selecting appropriate management objectives and harvest regulations. Received June 11, 2014; accepted September 4, 2014